SARS-CoV-2 Reinfection: Two Different Possible Presentations of Disease. Our Experience in a Province of Northern Italy - Nicolò, Fabbri; Salvatore, Greco (International Journal of Innovative Research in Medical Science, 2020)
COVID-19, the disease following SARS-CoV-2 infection, is the most important sanitary concern of the last decade. Many aspects of the infection are still unclear, such as the possibility of the virus to infect patients again after the first contact with the host and recovery. The current literature does not give fully answers about it; some dedicated reports were published recently even if SARS-CoV-2 reinfection remains an anecdotic event, difficult to confirm because of the intrinsic limitations of disease diagnostic methods. In this article we report our experience with COVID-19 inpatients who were suspected to be reinfected by SARS-CoV-2. They were both rehospitalized after a period of good health following COVID-19 recovery but they presented at the second hospital admission in two different ways. The first patient presented at the re-admission without a new viral RNA detection to pharyngeal swab, but with the radiographic findings of disease worsening; the second patient presented instead with a new positive swab but without any radiographic sign of COVID-19 worsening. It is still to determine whether a SARS-CoV-2 reinfection is a common, undiagnosed event, or it is a rare event affecting a very little number of patients. Drawing conclusions from single case reports is hard, but the aim of this little work is to raise clinicians’ awareness of a problem that is still far to be solved.